Palaeohydrology of the Lower Cretaceous pre-salt lacustrine system, from rift to post-rift phase, Santos Basin, Brazil - Pietzsch, Raphael; Oliveira, Daniel M.; Tedeschi, Leonardo R.; Queiroz Neto, João V.; Figueiredo, Milene F.; Vazquez, Joselito C.; de Souza, Rogério Schiffer (Palaeogeography, palaeoclimatology, palaeoecology, 2018)
Large oil accumulation discoveries in the last decade in the pre-salt rock succession off the Brazilian coast aroused renewed interest in carbonate reservoirs, prompting several studies aiming at unravelling the conditions of formation of these rocks. Despite that, there are still many gaps in the knowledge concerning environmental conditions of the deposition of the pre-salt carbonates of Santos Basin, located at the southeastern Brazilian margin. In this study, we present and discuss a new suite of geochemical and biostratigraphic data of the lacustrine rift to post-rift succession (broadly correlated with Itapema and Barra Velha Formations) of the Santos Basin, whose deposition occurred in the Aptian. The integration of the petrographic, biostratigraphic and geochemical data serves the ultimate purpose of the study, which is to apply the new radiogenic strontium data as a proxy for the reconstruction of the evolution of the lake hydrology associated with the deposition of the carbonates of the Itapema and Barra Velha Formations. These data are integrated into numerical models, whose results bring new ideas on the general hydrologic conditions of the lake system and on its evolution through time. The mass balance calculations indicate that two end-members alone can account as potential sources of Sr to the palaeolake: a mafic and a felsic component, respectively. The latter likely contributed with significantly higher fluxes, roughly one to two, and up to four, orders of magnitude higher than the former end-member for most of the depositional history in order to generate the 87Sr/86Sr trends observed in the carbonate rocks. Finally, the results obtained from the integration of the observations with the numerical models point to decreasing fluxes of water with time as contributed from both sources, suggesting that the formation of the deposits became very likely constrained to progressively more evaporitic and alkaline lake waters. These results also open up a new window into the environmental conditions of the interior Gondwana continent immediately prior to the definitive opening of the South Atlantic Ocean. [Display omitted] •We present geochemical and biostratigraphic data of the pre-salt of the Santos Basin.•Our new 87Sr/86Sr data show increasingly radiogenic values upwards in the profile.•The data are integrated in a series of numerical models to explain the general basin hydrology.•Our results suggest more evaporitic and alkaline lake waters in general with time.